2021
DOI: 10.1017/s1474747220000402
|View full text |Cite
|
Sign up to set email alerts
|

Social security and endogenous demographic change: child support and retirement policies

Abstract: This paper studies retirement and child support policies in a small, open, overlapping-generations economy with PAYG social security and endogenous retirement and fertility decisions. It demonstrates that neither fertility nor retirement choices necessarily coincide with socially optimal allocation, because agents do not take into account the externalities of fertility and the elderly labor supply in the economy as a whole. It shows that governments can realize the first-best allocation by introducing a child … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…We found that receipt of the NRP in rural families had positive and significant impacts on the physical health level of children, in that it can greatly decrease the number of medical visits. This echoed other studies regarding the value and impact of social pensions on child health in China [ 34 ] and in other countries [ 17 , 18 , 45 ], demonstrating the vital role that social pensions play in the physical health of family members other than the receiver. The reason for this is that, when the rural elderly receive the NRP—which can be regarded as an additional source of family income [ 65 ]—their labor burden is reduced and their daily leisure time is increased [ 43 ].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…We found that receipt of the NRP in rural families had positive and significant impacts on the physical health level of children, in that it can greatly decrease the number of medical visits. This echoed other studies regarding the value and impact of social pensions on child health in China [ 34 ] and in other countries [ 17 , 18 , 45 ], demonstrating the vital role that social pensions play in the physical health of family members other than the receiver. The reason for this is that, when the rural elderly receive the NRP—which can be regarded as an additional source of family income [ 65 ]—their labor burden is reduced and their daily leisure time is increased [ 43 ].…”
Section: Discussionsupporting
confidence: 65%
“…However, research on the effects of social pensions on the health of grandchildren remains limited. Although recent studies [ 17 , 18 ] have begun to pay attention to the relationship between social pensions and elderly’s grandchildren’s physical health, the findings of these studies need further verification. Moreover, the effects of social pensions on elderly’s grandchildren’s mental health have been largely ignored, thus calling for more investigation.…”
Section: Introductionmentioning
confidence: 99%
“…These scenarios were chosen because they are reminiscent of some of the principal policies that have been put into place over the past few years by various governments with the aim of reinforcing the financial sustainability of their respective pension systems. In fact, over the past two decades, the majority of OECD countries have raised the retirement age as a common reform (see Cipriani and Fioroni, 2022). Moreover, reducing incentives to retire early and rewarding employment at an older age to increase retirement age, have been put in place by various countries (OECD, 2019b).…”
Section: Numerical Examplesmentioning
confidence: 99%
“…Overall, these models focus on fertility and education policies, but do not consider retirement choices and therefore ignore the interaction between child policies and those devoted to increasing labour supply in old age. We add to this literature by extending the framework developed by Cipriani and Fioroni (2022) to include investment in human capital. To the best of our knowledge, no study to date has analyzed the optimal policies that aim to attain the first-best allocation and their welfare implications in a PAYG pension system with elderly labour supply and both endogenous education and fertility.…”
Section: Introductionmentioning
confidence: 99%
“…We expand previous overlapping generations (OLG) models [17] by including debt. The consideration of cycle government debt obligates the central planner to make sure that future generations will not be used as a heavy tax source.…”
Section: The Government and The Participants' Interestsmentioning
confidence: 99%